Blame Avoidance Strategies of Multiple Administrative Agencies During Policy Failure: A Case Study of Taiwan's 2014 Waste Oil Scandal. Issue 4 (April 2021) - Wang, Hongwung; Tsai, Yi-Ching
This study examines the blame avoidance (BA) strategies that may be adopted after policy failures of multiple agencies. A classification of agencies is proposed based on two factors: the amount of actual responsibility that an agency is obliged for, and the extent of an agency's perceived responsibility. Agencies can thus be classified into four types, which may have different tactical goals and specific BA strategies that contradict other agencies' goals, thereby leading to a complicated interaction between them. The results show that one of the three related agencies does not adopt suggested BA strategy and therefore fails to avoid blame.